2023
DOI: 10.3389/fendo.2023.1266641
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated gene mutation of EcIAG leads to sex reversal in the male ridgetail white prawn Exopalaemon carinicauda

Miao Miao,
Shihao Li,
Jianbo Yuan
et al.

Abstract: In the culture of crustaceans, most species show sexual dimorphism. Monosex culture is an effective approach to achieve high yield and economic value, especially for decapods of high value. Previous studies have developed some sex control strategies such as manual segregation, manipulation of male androgenic gland and knockdown of the male sexual differentiation switch gene encoding insulin-like androgenic gland hormone (IAG) in decapods. However, these methods could not generate hereditable changes. Genetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…1 ), short reproductive cycle, large eggs (diameters ranging 0.57–1.08 mm) and ease of culturing and breeding in captive conditions 8 . Currently, CRISPR/Cas9-mediated genome editing technology has been successfully used in E. carinicauda , which is the first time that gene editing has been realized in a decapod crustacean 9 , 10 . However, the absence of genomic data limits the further application of gene editing in studying the molecular biology, cytobiology and genetics of crustaceans.…”
Section: Background and Summarymentioning
confidence: 99%
“…1 ), short reproductive cycle, large eggs (diameters ranging 0.57–1.08 mm) and ease of culturing and breeding in captive conditions 8 . Currently, CRISPR/Cas9-mediated genome editing technology has been successfully used in E. carinicauda , which is the first time that gene editing has been realized in a decapod crustacean 9 , 10 . However, the absence of genomic data limits the further application of gene editing in studying the molecular biology, cytobiology and genetics of crustaceans.…”
Section: Background and Summarymentioning
confidence: 99%
“…Recently, Molcho et al reported the first genomic editing platform in M. rosenbergii, presenting a CRISPR protocol through direct injection into one-to four-cell embryos, which results in entire organism genome editing [127]. In the prawn E. carinicauda, knocking out EcIAG and obtaining homozygous mutants with biallelic mutations led to sex reversal from males to neo-females, suggesting CRISPR/Cas9 genome editing as an effective tool for sex manipulation in crustaceans, further supporting monosex aquaculture [128]. However, the transformation of applied technologies from RNAi interventions that do not affect the genome into genetically modifying methods is debatable.…”
Section: Molecular and Genomic Implicationsmentioning
confidence: 99%